Intake of sucrose solution and paradoxical sleep deprivation in the rat - Pezzato, Fernanda Augustini [UNESP]; De Paula, Hugo Garrido Medeiros [UNESP]; Bosqueiro, José Roberto [UNESP]; Hoshino, Katsumasa [UNESP] (My University, 2009)
Background: Paradoxical sleep deprivation (PSD) is known for its antidepressive property, both in humans and experimental animals. The small platform method used to promote PSD in rats, however, involves stress similar to that observed in the methods used to induce depressive-like state. Objective and methods: As sucrose solution intake is validated as a depressive-state marker in the rat, the present study evaluated such parameter before, during and after PSD carried out by the small platform method. Results: The daily mean sucrose solution (15%) ingested by a group of 11 adult male Wistar rats was progressively reduced with PSD. The daily fall in sucrose intake was statistically significant (t-test, p<0.05) from baseline, except in the second day of PSD. The development of taste aversion does not explain the reduction in sucrose intake, since its consumption, 2 days after the end of 4 days of PSD (n=5), was similar to baseline levels. PSD until the animals ceased to stay on the platform (n=6) showed to promote deaths in the recovery period with low consumption of sucrose. Conclusion: The relationship of the data obtained with the development of anhedonia and carbohidrate metabolism opens new interesting aspects for investigation.
Keywords: Anhedonia; Method; Rats; Sleep deprivation; Stress; Sucrose intake